BENEFITS OF FINANCIAL REPORTING FOR LOCAL BRAND MSMEs - Annisa Nadiyah Rahmani (Kajian Akuntansi, 2023)
The benefits of financial reporting for local brand MSMEs are important for the company's financial condition and provide the information for making appropriate and credible decisions in the company. The research here aims to provide the benefits of financial reporting for MSMEs, especially local brand MSMEs. This research is a descriptive study. The author uses data-supporting documents for compiling financial reports that will be used as output in the form of financial information. Researchers make comparisons between MSME entrepreneurs before having financial reports and after having financial reports. The research samples here are from eight local brands in the city of Bandung, namely HAICLO, Happy Go Lucky, Cherish the Love, Nazmi Indonesia, Dressofia, Lederweren Footwear, Hyka Studio, and Curva. The results of the study show that local brands can grow their businesses if they prepare financial reports and get investor funding and financial institutions to help with their financial and business strategies in the short and long term.